Generating advances in incomes and nutrition through sweetpotato (GAINS) - Odisha state, India. - International Potato Center (International Potato Center, 2019)
Sweetpotato, particularly orange-fleshed varieties, has under-exploited potential to improve nutrition and help build resilience to climate change among poor farming families across India. This project, which aims to improve food security, nutrition, and livelihoods in Odisha state, was first implemented in 2013 and has now moved to phase II.